Human health and climate change - an evolving discourse: A bibliometric citation analysis of top-cited articles within health sciences databases - Maya R. Kolsky; Ehud Grossman; Yuval Levy; Eyal Klang (Elsevier, 2023)
Background: The body of scientific literature on climate change and human health has exponentially grown over the past two decades, outlining a diverse list of health risks, vulnerable populations, protocols, and public policy frameworks. However, not all of these topics resonated equally among the health sciences community. This bibliometric citation analysis sets out to explore the priorities and interests reflected in the top cited articles on climate change and human health. Methods: We searched the PubMed database for all publications containing the term ''climate change'' in either title, abstract, or keywords, published after January 1st, 2009. The NCBI Entrez API was used to collect citation counts for the retrieved articles. The search yielded 55,590 articles. The top 200 cited publications were manually analyzed and classified according to topic and type of article. Findings: : Out of the 200 top-cited articles containing "Climate change" in either the title, abstract, or keywords, 40 articles engaged directly with human health or food security, receiving a total of 13,857 citations, with a range of 233-1865 citations (mean = 407.5, median = 316). Only 11 of the 40 articles were original studies. Infectious diseases were discussed in 24 of the 40 articles - 23 discuss vector-borne diseases. In comparison, only 11 refer to temperature extremes, 10 discuss nutritional insecurity and only 3 discuss migration and climate refugees. 50.9 % of all citations were published in either "Science" or "The Lancet". Interpretation: While climate change and human health had captured the attention of public policymakers, the consistent selection of resources and topics - favoring the Lancet commissions over environmental health publications and the IPCC, citing infectious diseases more frequently than mental health, air pollution, and extreme weather, and the overall relatively low number of citations - could indicate a low level of interest amongst the broader health sciences community.